Faith Education According to Taqiyuddin an-Nabhani: Analysis of the Contents of the Book Nizham al-Islam (Pendidikan Aqidah Menurut Taqiyuddin an-Nabhani: Analisis Isi Kitab Nizham al-Islam)) - Dirman, Dirman (Shautut Tarbiyah-IAIN Kendari, 2024)
AbstractFaith education is an important aspect in the life of a Muslim. The concept of faith education, according to Shaykh Taqiyuddin an-Nabhani, offers an in-depth view of the importance of correct understanding of religious beliefs in the lives of individuals and society. The main emphasis in this concept is to build a strong foundation in religious beliefs as a foundation for Muslim individuals. According to Shaikh Taqiyuddin an-Nabhani, faith education starts from an early age and includes learning about the Koran, hadith, the pillars of faith, the concept of monotheism, the characteristics of Allah, as well as the social and political context in Islam. This concept also emphasizes the harmonious relationship between religion and science. Good religious education can help individuals develop strong beliefs, a deep understanding of religious teachings, and awareness of their role in realizing a political system based on Islamic values. The aim of this research is to examine the concept of aqidah education according to Syaikh Taqiyuddin an-Nabhani in the book Nidzamul Islam. This research is library research with the research object being the book Nizham al-Islam. The research approach used is a content analysis approach. The results of the research show that the aqidah education contained in the book Nizham al-Islam is: to obtain true faith, humans must make their faith emerge from the thought process, always research and pay attention and always refer to their reason and believe in the existence of Allah SWT. Aqidah explains that behind the universe, humans and life there is a creator (al-Khaliq) who has created all three, and who has created everything else. He is Allah SWT. That the creator has created everything from nothing into existence. The book of the Koran comes from Allah SWT.Keywords: Faith Education, Taqiyuddin An Nabhani, Nidzamul Islam Book